The 1977 Tundra Fire in the Kokolik River Area of Alaska - Hall, Dorothy K.; Brown, Jerry; Johnson, Larry (ARCTIC, 1978)
Widespread fires occurred on the Seward Peninsula, Alaska, during the summer of 1977. During this period there was also one large natural fire in the northern part of the state. Presumably caused by lightening, it occurred due east of Point Lay and several kilometres southwest of the Kokolik River (69 30 N, 161 50 W) on the boundary between the coastal plain and the northern foothills . This was the farthest north a fire had ever been fought by the personnel of BLM in Alaska. No tundra fires had previously been reported from this area, . Climatic conditions in northern and western Alaska during the summer of 1977, . were apparently ideal for tundra fires. The information on the spread of the fire, as presented in this short paper, was gathered from Landsat imagery, meteorological observations, facts concerning the natural containment of the fire, and investigations of the affected area following the fire.